(untitled) (Medical Forum Monthly, 2022)
Objective: The purpose of this study was to find out how often oral pain is during pregnancy. Study Design: Cross-sectional observational study Place and Duration of Study: This study was conducted at the Dental OPD of Chiniot General Hospital Korangi Karachi from Nov 2019 to July 2020 for a period of nine months. Materials and Methods: This study was initially designed to include 150 pregnant females but due to COVID -19 situation and OPDs closure restrict many pregnant females for their dental check-ups and appointments in Dental OPDs. Thus, the data collected of 90 participants including all stages of pregnancy and the analysis was done on the results of 90 participants. Before the commencement of data collection, each participant was given an informed consent. Results: Among the study participants (n=90) who sought dental care, 64 (71.1%) presented with dental pain while 26(28.9%) presented with periodontal symptoms. Conclusion: A high prevalence of dental pain was observed among pregnant women and dental caries was the most specific determinant of the dental pain.